Balance control of planar biped robots using virtual holonomic constraints. Issue 6 (15th August 2014) - Hu, Yong; Lin, Zhiyun
SUMMARY: The balance control problem of planar bipedal robots during disturbed standing is investigated. Virtual holonomic constraints which specify the angles of actuated joints as a function of the rotation angle between the sole of the stance foot and the ground are recalled. These constraints enable the robot to avoid turnover during external disturbances similar to how a human being would react. Moreover, for a disturbance beyond the balance conditions for single-leg support, the robot changes to a double support posture to avoid turnover by the virtual holonomic constraints. Further, for a special kind of balance: standing on toe which leads to underactuation, we also give the design conditions of the virtual holonomic constraints.